Design and Synthesis of Bisulfone-Linked Two-Dimensional Conjugated Microporous Polymers for CO2 Adsorption and Energy Storage - Mohamed Gamal Mohamed; Siang-Yi Chang; Moshin Ejaz; Maha Mohamed Samy; Aya Osama Mousa; Shiao-Wei Kuo (Molecules, 2023)
We have successfully synthesized two types of two-dimensional conjugated microporous polymers (CMPs), Py-BSU and TBN-BSU CMPs, by using the Sonogashira cross-coupling reaction of BSU-Br2 (2,8-Dibromothianthrene-5,5′,10,10′-Tetraoxide) with Py-T (1,3,6,8-Tetraethynylpyrene) and TBN-T (2,7,10,15-Tetraethynyldibenzo[g,p]chrysene), respectively. We characterized the chemical structure, morphology, physical properties, and potential applications of these materials using various analytical instruments. Both Py-BSU and TBN-BSU CMPs showed high thermal stability with thermal decomposition temperatures (Td10) up to 371 °C and char yields close to 48 wt%, as determined by thermogravimetric analysis (TGA). TBN-BSU CMPs exhibited a higher specific surface area and porosity of 391 m2 g−1 and 0.30 cm3 g−1, respectively, due to their large micropore and mesopore structure. These CMPs with extended π-conjugated frameworks and high surface areas are promising organic electroactive materials that can be used as electrode materials for supercapacitors (SCs) and gas adsorption. Our experimental results demonstrated that the TBN-BSU CMP electrode had better electrochemical characteristics with a longer discharge time course and a specific capacitance of 70 F g−1. Additionally, the electrode exhibited an excellent capacitance retention rate of 99.9% in the 2000-cycle stability test. The CO2 uptake capacity of TBN-BSU CMP and Py-BSU CMP were 1.60 and 1.45 mmol g−1, respectively, at 298 K and 1 bar. These results indicate that the BSU-based CMPs synthesized in this study have potential applications in electrical testing and CO2 capture.